Planning of work on the management of household waste landfills at the level of the territorial community - Illiash, Oksana; Zhuravel, Taras; Peretiatko, Petro (Academic journal Industrial Machine Building Civil Engineering, 2022)
Taking into account the existing experience of waste management in the EU countries, Poltava region is gradually implementing the practice of a cluster (subregional) approach, launched by the Deutsche Gesellschaft für Internationale Zusammenarbeit (GIZ) GmbH project as part of the international project "Municipal Reform in Eastern Ukraine". Within the framework of this research, an approach to assessing the condition of landfills was proposed and tested on the example of the Novoorzhytska community in Poltava Oblast, based on which the landfills were classified, the status of each landfill was determined, and appropriate recommendations were made for their further closure/liquidation or the possibility of reconstruction/maintenance and further controlled operation